Moderating role of extrinsic and intrinsic motivations in the relationship between community leadership and social capital in rural Malaysia - Md Rami, Ahmad Aizuddin; Zaremohzzabieh, Zeinab; Aziz, Faiq; Ismail, Ismi Arif; Abdullah, Haslinda (MDPI AG, 2022)
(1) Background: Social capital linking, bridging, and bonding have become fascinating options for sustainable development in rural Malaysia. (2) Objective: The aims of this research were (i) to evaluate how leadership styles affect the social capital in rural Malaysia, and (ii) to examine the moderating role of motivation in enhancing these relationships. (3) Methods: The researchers utilized a quantitative approach to analyze data collected through a self-administered survey involving 190 members of the Village Development and Security Committee (JKKK) in Malaysia. The concept of “leadership quality” was measured based on transformational, transactional, and laissez-faire leadership, while “motivations” cover its extrinsic and intrinsic components. The data were analyzed using a structural equation modeling (SEM) technique. (4) Results: The findings reveal that transformational, transactional, and laissez-faire leadership types are essential to increase social capital in rural Malaysia. It may therefore be suggested that community leadership and its effective styles should be nurtured within the rural community to address more complex problems regarding social capital development. On top of that, extrinsic and intrinsic motivations also appeared to be significant moderating factors in determining social capital development in rural Malaysia. (5) Conclusions: Based on the results, community leaders with different leadership styles may offer better social benefits to the rural community by using various incentives to engage rural residents in facilitating social activities. (6) Policy recommendations: This study suggests further implications for academics and policy makers focused on social capital for sustainable rural development in Malaysia.